Modulation of reproductive exhaustion using Ulva clathrata in Pacific white shrimp Litopenaeus vannamei (Boone, 1931) broodstock during commercial maturation. (26th September 2018) - Corral‐Rosales, Diana Cristina; Cruz‐Suárez, Lucia Elizabeth; Ricque‐Marie, Denis; Rodríguez‐Jaramillo, Carmen; Palacios, Elena
Abstract: Ulva clathrata meal (2%) was supplemented in a fresh maturation diet for Litopenaeus vannamei broodstock in a commercial larval facility and its effects on reproductive performance, histology and histochemistry of gonad, and biochemical composition of gonad, hepatopancreas, and muscle were analysed. Females that were given Ulva in the diet had reduced mortality compared to controls, with no differences in males. Females fed Ulva also had bigger oocytes but only those in late vitellogenesis (+7%, p  < 0.01) and postvitellogenesis (+15%, p  < 0.01); they also had a higher proportion of late vitellogenic oocytes in maturation stage II, and a bigger area occupied by cortical rods. No significant differences were found for the proportion of previtellogenic or early vitellogenic oocytes per maturation stage or as a result of Ulva . Females fed Ulva had higher levels of lipids in ovary (+35%, p  < 0.05), with no significant differences in biochemical reserves in hepatopancreas or muscle. The total number of eggs (+5%, p  < 0.01), nauplii per spawn (+18%, p  < 0.01), and hatching rate (+13%, p  < 0.01) during the productive cycle were higher for Ulva fed shrimp. Individual follow‐up of marked females during the productive cycle showed a decreased reproductive exhaustion in females fed Ulva over consecutive spawns. Apparently, U. clathrata stimulates advanced vitellogenesis by improving lipid accumulation in gonads, and this in turn increases reproductive performance: inclusion of this algae in shrimp diet could be used to decrease reproductive exhaustion during production.